IMPLEMENTASI PEMBINAAN DAN PEMBERDAYAAN JASA KONSTRUKSI DALAM PENGELOLAAN TENAGA KERJA PADA DINAS PEKERJAAN UMUM, PERUMAHAN DAN KAWASAN PERMUKIMAN KABUPATEN PONOROGO - Wantini, Tri (JI@P, 2021)
This thesis is motivated by the need for construction workers in Ponorogo Regency who must have work competency certificates such as Work Skills Certificate. Based on data from the Public Works, Housing and Settlement Service (PUPKP) of Ponorogo Regency in the past three years there are around 700 construction workers, but there are more than 500 construction workers who are still in the process of obtaining Work Skills Certificate (SKT). This study aims to describe and to analyze the implementation of coaching and empowerment of construction services in the management of the construction workforce at the PUPKP Office of Ponorogo Regency. The theory used to analyze the implementation of development and empowerment of construction services in managing the workforce at the PUPKP Office of Ponorogo Regency uses a model of public policy implementation according to Van Metter and Van Horn. This study uses a descriptive method with a qualitative approach. Research informants using purposive sampling technique. Data collection techniques using observation, in-depth interviews, and documentation. The data analysis technique used interactive analysis consisting of data reduction, data presentation and conclusion drawing. The validity of the data used source triangulation. The results of this study were obtained from six indicators of public policy implementation according to Van Metter and Van Horn, showing that it fulfills expectations, where the performance of the construction workers who are fostered can be more skilled, competent and can improve the quality of their work.